Financial Expectations and Household Consumption: Does Middle Inflation Matter? - Sarah Brown; Mark N. Harris; Christopher Spencer; Karl Taylor (Institute of Labor Economics (IZA), 2020)
Using British panel data, we explore the finding that households often expect theirÂ…financial position to remain unchanged compared to other alternatives, using a generalised middle inflated ordered probit (GMIOP) model. In doing so we account for the tendency of individuals to choose 'neutral' responses when faced with attitudinal and opinion-based questions, which are a common feature of survey data. Our empirical analysis strongly supports the use of a GMIOP model to account for this response pattern. Expectations indices based on competing discrete choice models are then exploited to explore the role that financial expectations play in driving the consumption of different types of durable goods and the amount of expenditure undertaken. Whilst financial optimism is significantly associated with consumption, indices which fail to take into account middle-inflation overestimate the impact of financial expectations.
Keywords: C12; C35; 330; household consumption; financial expectations; survey data; generalised middle-inflated ordered probit model